Presentation and validation of a new optical sensing concept based in a 3d-printing solution - Pimentel, Anthony Michael Fernandes (2018)
In high competitive markets, such as the automotive industry, the better quality of products, reduction of manufacturing costs and the fulfilment of all delivery deadlines can only be achieved through continuous improvement of production capabilities. One current strategy is to develop and create smarter and adaptive assembly tools. Automation is a relevant area of development in the current industrial world and the baseline of the fourth industrial revolution (Industry 4.0). Namely, it is very important to use sensing components on jigs for assembly parts in the production line. The arrangement of sensing components on the assembly tools is very dependent of the product, making the project more complex and less flexible. This issue can penalise the productivity heavily, especially if a wide range of products and changeover operations are usual. The use of Additive Manufacturing (AM) is growing in the industry and offers a high potential for research and development in the present stage. The AM is advantageous in many areas, especially in the rapid construction of complex tools (RP). This paper presents a new optical sensing concept based on the 3D printing of internal circuits in the assembly tools. This solution can bring many advantages and increase tools flexibility.